Pulmonary manifestations of Sjögren's syndrome. (June 2016) - Flament, Thomas; Bigot, Adrien; Chaigne, Benjamin; Henique, Helene; Diot, Elisabeth; Marchand-Adam, Sylvain
In 9–20% of cases, Sjögren's syndrome is associated with various respiratory symptoms. The most typical manifestations are chronic interstitial lung disease (ILD) and tracheobronchial disease. The most common manifestation of ILD is nonspecific interstitial pneumonia in its fibrosing variant. Other types of ILD, such as organising pneumonia, usual interstitial pneumonia and lymphocytic interstitial pneumonitis, are rare. Their radiological presentation is less distinctive, and definitive diagnosis may require the use of transbronchial or surgical lung biopsy. Corticosteroid therapy is the mainstay of ILD treatment in Sjögren's syndrome, but the use of other immunosuppressive drugs needs to be determined. ILD is a significant cause of death in Sjögren's syndrome. Tracheobronchial disease is common in Sjögren's syndrome, characterised by diffuse lymphocytic infiltration of the airway. It is sometimes responsible for a crippling chronic cough. It can also present in the form of bronchial hyperresponsiveness, bronchiectasis, bronchiolitis or recurrent respiratory infections. The management of these manifestations may require treatment for dryness and/or inflammation of the airways. Airway disease has little effect on respiratory function and is rarely the cause of death in Sjögren's syndrome patients. Rare respiratory complications such as amyloidosis, lymphoma or pulmonary hypertension should not be disregarded in Sjögren's syndrome patients. We present the features, diagnostic tests and treatments of thoracic manifestations of Sjögren's syndrome http://ow.ly/10m8vd